PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SUZUKI PADA CV.GAJAH MADA CABANG PADANG - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to review to find out how big the influence product quality, Brand Image Products And Promotion Operating simultaneous and partial Buying Decision Against Suzuki motorcycle IN CV.Gajah Mada Padang Branch.Data collection method through primary data and secondary data in form of interviews, collection, distributing questionnaires and data from the Company. The analytical method used is the analysis of correlation and regression analysis, to review Namely hypothesis test used t test and F test. Research results show that the products are quality Positive Influence Buying Decision Against Suzuki motorcycle in CV.Gajah Mada Padang Branch. Then, There is a significant positive effect And Brand Image Buying Decision Against Suzuki motorcycle in CV.Gajah Mada Branch Padang and are positive and significant influence Campaign Against Buying Decision Suzuki motorcycle in CV.Gajah Mada Padang Branch Operation Together And There The significant influence between Product quality, Brand and Promotion. The decision to purchase a motorcycle that Suzuki in CV.Gajah Mada Branch field.